Let us solve the givenexpression:
= 2 [5C0 (2√x)0 + 5C2 (2√x)2 + 5C4 (2√x)4]
= 2 [1 + 10 (4x) + 5(16x2)]
= 2 [1 + 40x + 80x2]
Let us solve the givenexpression:
= 2 [6C0 (√2)6 + 6C2 (√2)4 + 6C4 (√2)2 + 6C6 (√2)0]
= 2 [8 + 15 (4) + 15(2) + 1]
= 2 [99]
= 198
Let us solve the givenexpression:
= 2 [5C1 (34)(√2)1 + 5C3 (32)(√2)3 + 5C5 (30)(√2)5]
= 2 [5 (81) (√2) + 10 (9) (2√2) + 4√2]
= 2√2 (405 + 180 + 4)
= 1178√2
Let us solve the givenexpression:
= 2 [7C0 (27)(√3)0 + 7C2 (25)(√3)2 + 7C4 (23)(√3)4 + 7C6 (21)(√3)6]
= 2 [128 + 21 (32)(3)+ 35(8)(9) + 7(2)(27)]
= 2 [128 + 2016 + 2520+ 378]
= 2 [5042]
= 10084
Let us solve the givenexpression:
= 2 [5C1 (√3)4 + 5C3 (√3)2 + 5C5 (√3)0]
= 2 [5 (9) + 10 (3) +1]
= 2 [76]
= 152
Let us solve the givenexpression:
= (1 – 0.01)5 +(1 + 0.01)5
= 2 [5C0 (0.01)0 + 5C2 (0.01)2 + 5C4 (0.01)4]
= 2 [1 + 10 (0.0001) +5 (0.00000001)]
= 2 [1.00100005]
= 2.0020001
Let us solve the givenexpression:
= 2 [6C1 (√3)5 (√2)1 + 6C3 (√3)3 (√2)3 + 6C5 (√3)1 (√2)5]
= 2 [6 (9√3) (√2) + 20 (3√3) (2√2) + 6 (√3) (4√2)]
= 2 [√6 (54 + 120 + 24)]
= 396 √6
= 2 [a8 +6a6 – 6a4 + a4 + 1 – 2a2]
= 2a8 +12a6 – 10a4 – 4a2 + 2